2016
DOI: 10.1093/mnras/stw130
|View full text |Cite
|
Sign up to set email alerts
|

The fate of high-redshift massive compact galaxies

Abstract: Massive high-redshift quiescent compact galaxies (nicknamed red nuggets) have been traditionally connected to present-day elliptical galaxies, often overlooking the relationships that they may have with other galaxy types. We use large bulge-disk decomposition catalogues based on the Sloan Digital Sky Survey (SDSS) to check the hypothesis that red nuggets have survived as compact cores embedded inside the haloes or disks of present-day massive galaxies. In this study, we designate a compact core as the bulge c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 96 publications
8
58
0
1
Order By: Relevance
“…This is a simple and elegant solution which has since been supported by the results in de la Rosa et al (2016) and Margalef-Bentabol et al (2016). Moreover, it matches with evidence for nascent disks at high-z (e.g.…”
Section: Compact Massive Spheroids -Evolution or Notsupporting
confidence: 80%
See 1 more Smart Citation
“…This is a simple and elegant solution which has since been supported by the results in de la Rosa et al (2016) and Margalef-Bentabol et al (2016). Moreover, it matches with evidence for nascent disks at high-z (e.g.…”
Section: Compact Massive Spheroids -Evolution or Notsupporting
confidence: 80%
“…Dullo & Graham (2013) further advocated that disks may have formed in and around these high-z mass concentrations to build the local lenticular galaxies. Nearly two dozen z ≈ 0 galaxies with massive compact spheroidal components have since been presented in Graham, Dullo & Savorgnan (2015, hereafter GDS15; see also Valentinuzzi et al 2010a,b;Poggianti et al 2013a,b;Saulder et al 2015;Carollo et al 2016;de la Rosa et al 2016). This sample included early-type galaxies in which the disk had not grown into a largescale disk that dominates the light at large radii but was instead an intermediate-scale disk 1 embedded within the spheroidal component of the galaxy 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Because r eff > r h here, our models have a somewhat massive central region, which may stem from the formation process, as the galaxies do not grow, but form in practically one monolithic collapse. These compact bulges may also be related to the observed red nuggets (de la Rosa et al 2016). This feature of our models will also be important in Section 4.6, where we show that they slightly lack stellar angular momentum.…”
Section: Comparison Between Newtonian and Mondian Modelsmentioning
confidence: 76%
“…As far as the remaining 25% of dense ETGs possibly missing in the local Universe, stochastic merger events could have transformed them into non-dense systems (Σ ≤ 2500 M pc −2 ), contributing to the increase of the mean size and the number density of the whole population of ultramassive ETGs at z < 1.5. In fact, de la Rosa et al (2016) have found that a portion of presentday massive galaxies host in the centre a compact core with the same structural and dynamical properties as high-z compact galaxies. Numerically, the contribution of these size-evolved ultramassive dense ETGs to the total number density of local ultramassive ETGs is ∼2 × 10 −5 gal/Mpc3 (see Fig.…”
Section: Discussionmentioning
confidence: 99%